Meeting of the apical and basolateral endocytic pathways of the Madin- Darby canine kidney cell in late endosomes (The Rockefeller University Press, 1989)
Electron microscopic approaches have been used to study the endocytic pathways from the apical and basolateral surface domains of the polarized epithelial cell, MDCK strain I, grown on polycarbonate filters. The cells were incubated at 37 degrees C in the presence of two distinguishable markers administered separately to the apical or the basolateral domain. Initially each marker was visualized within distinct apical or basolateral peripheral endosomes. However, after 15 min at 37 degrees C, both markers were observed within common perinuclear structures. The compartment in which meeting first occurred was shown to be a late endosome (prelysosome) that labeled extensively with antibodies against the cation-independent mannose-6-phosphate receptor (MPR) on cryosections. With increasing incubation times, markers passed from these MPR-positive structures into a common set of MPR-negative lysosomes that were mainly located in the apical half of the cell. A detailed quantitative analysis of the endocytic pathways was carried out using stereological techniques in conjunction with horseradish peroxidase and acid phosphatase cytochemistry. This enabled us to estimate the absolute volumes and membrane surface areas of the endocytic organelles involved in apical and basolateral endocytosis.